2022
DOI: 10.3389/fpubh.2022.844541
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Natural/Built Campus Environment and Depression Among Chinese Undergraduates: Multiscale Evidence for the Moderating Role of Socioeconomic Factors After Controlling for Residential Self-Selection

Abstract: AimEvidence on the association between natural-built environments and depression is largely derived from the general population and prone to residential self-selection bias because of the nature of cross-sectional research design. Despite emerging adulthood, which includes the university years, is a critical stage for forming life-long health habits, studies on this topic focusing on undergraduate students are limited. The current study aims to illustrate the underlying mechanisms for how the campus-based envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…The main findings were that in addition to blue and green spaces, gray, living, and study spaces were all restorative. According to previous studies, green space can reduce mental stress and relieve anxiety [ 14 , 15 , 16 ], and blue space is believed to contribute to recovery from mental illness and mental fatigue [ 19 , 20 ]. Overall, studies have shown that greater exposure to nature positively affects attentional recovery and stress reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main findings were that in addition to blue and green spaces, gray, living, and study spaces were all restorative. According to previous studies, green space can reduce mental stress and relieve anxiety [ 14 , 15 , 16 ], and blue space is believed to contribute to recovery from mental illness and mental fatigue [ 19 , 20 ]. Overall, studies have shown that greater exposure to nature positively affects attentional recovery and stress reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Blue spaces (a natural environment dominated by water bodies, which correspond to green spaces, e.g., wetlands, rivers, lakes, and ponds) are considered to have the best restoration potential among outdoor campus spaces [ 8 , 18 ]. In a campus-centered landscape study, Yang et al found a positive correlation between depression prevention and increased water coverage [ 19 ]. Natural elements can influence the resilience of an indoor space.…”
Section: Introductionmentioning
confidence: 99%
“…Even though we here offer a detailed approach to reduce inherent biases and further optimize ancestral trait reconstruction by subsampling large datasets, there are other procedures to account for issues with sampling, including careful research and surveillance design, simulations, and weighted methods based on metrics such as prevalence (10,(54)(55)(56)(57)(58). New methodological developments enable phylogeographic inferences that are not as affected by sampling bias ( 14), but currently do not scale well with the increasing number of sequences and locations, and hence make analysis of large data sets computationally challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Then, previous studies disproportionately center on the association of objective neighborhoods environment on SCB ( 24 ), whereas the effects of the subjectively measured neighborhood environment have been largely ignored, except for a few exceptions ( 4 , 11 ). According to Guo et al ( 11 ), subjectively measured neighborhood environments may contribute to SCB given that people would feel a greater connection to their community when they have a better perception and feeling of their living circumstances.…”
Section: Literature Reviewmentioning
confidence: 99%